Unlearned and learned behaviour of bumble bees in the absence of reward. - Simonds, Virginia M. (University of Ottawa (Canada), 2002)
In the absence of previous experience with flowers, how do bees distinguish between possible food sources and non-rewarding objects? Unrewarding stimuli (colours in Experiment 1 and patterns in Experiment 2) were presented in a radial arm maze. The unlearned approach responses of bumblebees (Bombus impatiens) were recorded and significant preferences were obtained: the bees chose yellow and blue over other colours, and radial patterns over concentric patterns or unpatterned discs. Habituation was demonstrated when choices proportions for the same pattern by the same bees decreased over two test sessions. When an attractive novel pattern was presented in the third session the trend was reversed. These data confirm both that truly naive bees have unlearned colour and pattern preferences and that learning not to approach these stimuli occurs in the absence of reward. Two further experiments tested the length of time that habituation is maintained by bumble bees and the degree to which contextual cues contribute to maintaining habituation. In Experiment 3 once bees habituated to a radial pattern response decrement was maintained after a stimulus presentation delay of two hours. After a 24 hour delay, however, the preference was restored. In Experiment 4 exposure to the context without stimulus presentation did not affect the retention of the habituated response. These findings confirm bumble bees' ability to habituate to a stimulus and delineate its time course as lasting in the range of minutes and hours but not days. They call into question the associative role of contextual cues in habituation for bumble bees.
Keywords: Biology, Entomology.